Становлення системи правосуддя у справах неповнолытных ( XIX - поч. XX ст. ) - Продіус, Костянтин Васильович; Продиус, Константин Васильевич; Prodyus, K. (My University, 2010)
In the offered article reasons of origin of courts are analysed for minor in the countries of Europe and America in the middle of XIX – beginning of XX century. Becoming organs of juvenile justice is examined, the basic models of courts are characterized for minor one, the distinguishing features of juvenile judiciary and legal proceeding are examined.
Продіус К. В. Становлення системи правосуддя у справах неповнолытных ( XIX - поч. XX ст. ) / К. В. Продіус // Актуальні проблеми політики : зб. наук. пр. / редкол. : С. В. Ківалов (голов. ред.), Л. І. Кормич (заст. голов. ред.), Ю. П. Аленін [та ін.] ; МОНмолодьспорт України, НУ ОЮА. - Одеса : Фенікс, 2010. - Вип. 40. - С. 518-525.
Keywords: система правосуддя у справах неповнолітніх; виникнення судів для неповнолітніх у странах Європи та Америки; органи ювенальної юстиції; моделі судів для неповнолітніх; відмінні риси ювенального судоустрою та судочинства; система правосудия в делах несовершеннолетних; возникновение судов несовершеннолетних в странах Европы и Америки; органы ювенальной юстиции; модели судов для несовершеннолетних; отличительные черты ювенального судоустройства и судопроизводства; the system of justice in juvenile cases; the occurrence of juvenile courts in the countries of Europe and America; juvenile justice agencies; model juvenile courts; the distinctive features of the juvenile judicial system and legal proceedings